PEMANFAATAN EKSTRAK KULIT KAKAO SEBAGAI ADITIF CAT UNTUK PENGENDALIAN LAJU KOROSI PADA PAKU KONSTRUKSI KAPAL KAYU - Harri Biora Putra; Jon Affi Affi; Gunawarman Gunawarman; Yuli Yetri (POLITEKNIK NEGERI BENGKALIS, 2018)
Corrosion on wooden nails is very detrimental because it shortens the life of the ship. Although the used spikes have been coated with corrosion resistance material, corrosion rate is still very harmful. Therefore that additional effort is required for reducing the corrosion rate of these spikes. Research has been done by comparing the giving of cocoa peels extract as a paint mixer to corrosion rate. As a comparison has also been done nails without paint and nails painted without additional cocoa peels extract. Calculation of corrosion rate is done by weight loss method. The addition of cocoa peels extract showed significant effect on corrosion rate, it can be explained cocoa peels containing secondary metabolite compound one of them is tannin. The tannin compound in the extract can form complex compounds with Fe (III) on the metal surface, so that the corrosion reaction rate will decreas.Keywords: cocoa peels extract, corrosion, weight loss.